„..Da kenn ich eine kleine Kirche.. da gehe ich rein.. bete ich türkisch…“. Modifikationen religiöser Identitäten bei Akademikerinnen türkischer Herkunft in Wien - Dursun, Sule (Interdisciplinary journal for religion and transformation in contemporary society, 2017)
The following paper aims to present religious identities of young, educated Turkish women in Vienna. Analysis of the interviews shows that university education leads to individual modification of religious and cultural practices as well as an adaptation of religious values and cultural attitudes in the lives of these women. The results show that young women - who were brought up in a conservative or popular Islamic way - developedamodified, individual understanding of their religion. The approach of religious reflexivity as a result of continuous confrontation with new experiences is the decisive result of the study. These young women reflected upon their upbringing/setting and relied on themselves and their own intuition to solve religious challenges.